Robust training attenuates TBI-induced deficits in reference and working memory on the radial 8-arm maze - Sebastian, Veronica; Diallo, Aissatou; Ling, Douglas S.; Serrano, Peter (Frontiers in Behavioral Neuroscience, 2013)
Globally, it is estimated that nearly 10 million people sustain severe brain injuries leading to hospitalization and/or death every year. Amongst survivors, traumatic brain injury (TBI) results in a wide variety of physical, emotional and cognitive deficits. The most common cognitive deficit associated with TBI is memory loss, involving impairments in spatial reference and working memory. However, the majority of research thus far has characterized the deficits associated with TBI on either reference or working memory systems separately, without investigating how they interact within in a single task. Thus we examined the effects of TBI on short-term working and long-term reference memory using the radial 8-arm maze (RAM) with a sequence of 4 baited and 4 unbaited arms. Subjects were given 10 daily trials for 6 days followed by a memory retrieval test two weeks after training. Multiple training trials not only provide robust training, but also test the subjects’ ability to frequently update short-term memory while learning the reference rules of the task. Our results show that TBI significantly impaired short-term working memory function on previously acquired spatial information but has little effect on long-term reference memory. Additionally, TBI significantly increased working memory errors during acquisition and reference memory errors during retention testing two weeks later. With a longer recovery period after TBI, the robust RAM training mitigated the reference memory deficit in retention but not the short-term working memory deficit during acquisition. These results identify the resiliency and vulnerabilities of short-term working and long-term reference memory to TBI in the context of robust training. The data highlight the role of cognitive training and other behavioral remediation strategies implicated in attenuating deficits associated with TBI.